2001
DOI: 10.2337/diacare.24.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Glycemic Control in Young People With Type 1 Diabetes in Scotland

Abstract: The overall glycemic control of diabetic young people in Scotland is equivalent to a Diabetes Control and Complications Trial HbA1c concentration of 8.7%, placing the majority at a high risk of the complications of diabetes in adulthood. Although factors were significantly associated with poor HbA1c adjustment for these did not explain the differences between centers. We suggest that factors not analyzed in DIABAUD2 (e.g., deployment of resources, organization of the clinical structure, strategies of care, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(20 citation statements)
references
References 14 publications
(10 reference statements)
6
14
0
Order By: Relevance
“…Older age, female sex, and longer diabetes duration were significantly associated with worse metabolic control, affirming previously reported findings (4,68,10,1316,21,2325). The varying quality of metabolic control may in part be attributable to differences in insulin sensitivity, treatment compliance, or insulin needs related to these factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Older age, female sex, and longer diabetes duration were significantly associated with worse metabolic control, affirming previously reported findings (4,68,10,1316,21,2325). The varying quality of metabolic control may in part be attributable to differences in insulin sensitivity, treatment compliance, or insulin needs related to these factors.…”
Section: Discussionsupporting
confidence: 90%
“…Further, in the current study, improvement in average HbA 1c over time was comparable for different treatment regimens. This supports the view that other factors, such as the development of multidisciplinary diabetes care teams and improvements in structural quality of diabetes care and patient education, may have accounted for the observed trend (8,21,22). …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…16 Likewise, the Diabaud 2 study found significant differences in HbA1c between 18 Scottish paediatric diabetes centres, also suggesting that care in some centres was better than others. 17 Deployment of resources, organisation of the clinic and strategies of medical care were suggested as possible reasons for the differences, but these factors could not be quantified by the study. Cultural factors have also been suggested as a significant factor affecting outcomes between centres.…”
Section: Which Factors Contribute To Better Care?mentioning
confidence: 94%
“…12 National audits of children's diabetes services and outcomes have revealed important data in the past, but in Scotland this has not been an ongoing audit. 3,17 To be fully effective it should be carried out continuously, be co-ordinated by a national body (for example, Paediatric Diabetes MCN) and be fully supported financially by the government.…”
Section: Evaluating Healthcarementioning
confidence: 99%